Nature of amyloid deposits in hypernephroma. Immunocytochemical studies in 2 cases associated with amyloid polyneuropathy. - Dalakas, M. C. (1984)
Two patients who presented with amyloid polyneuropathy were found to have an amyloid-positive hypernephroma. The amyloid extracted from the tumor of one patient was purified by gel filtration and found to immunoreact by immunodiffusion, only with antiserum against denatured lambda-type amyloid protein but not with antisera against denatured kappa amyloid, AA, or prealbumin. With the unlabeled immunoperoxidase method or immunofluorescence in combination with these specific antisera, it was shown that in both patients the amyloid deposits in the tumor, kidney, lymph node, muscle, and nerve had lambda-type amyloid antigenic fibril determinants. Some regions, amyloid-negative by congo red, immunoreacted with anti-lambda antiserum and were shown to represent amyloid fibrils electron microscopically. Several plasma cells found in the tumor and lymph node immunoreacted specifically with the anti-amyloid lambda antiserum. The findings provide the first observation that the amyloid in hypernephroma can be of immunocytic origin, even in the absence of overt signs of plasma cell dyscrasia, and suggest that amyloid polyneuropathy could be the presenting sign of hypernephroma.